Nine Values of Gus Dur to Build Harmonization in a Multicultural Society (Case Study in Candirenggo Village, Malang Regency) - Mustofa, Bisri; Fitrotulloh, M. Rofik (Budapest International Research and Critics University, 2022)
One of the negative effects of social media is that it spreads intolerance to villages, which play a role in shaping society into radicalism, and violent extremism. The Wahid Foundation designed an initiative called Desa Damai. Wahid Foundation was established to advance Gus Dur's vision of humanity Nine values to build moderate thinking that encourages the creation of democracy, multiculturalism, and peace. This research includes descriptive qualitative research and case studies in Candirenggo Village, Malang Regency. This research design uses grounded theory. Data were obtained from observation, in-depth interviews, and documentation and focus group discussions. The data analysis method used in this study is grounded theory. The results of the research are the implementation of the nine values of Gus Dur to build harmonization in the midst of a multicultural society as the basis for developing the indicators for Desa Damai and the basis for developing human resources who have moderate and tolerant characters towards other cultures. In addition, these nine values of Gus Dur contribute to building awareness as God's creatures, social beings and free, civilized souls.